2008
DOI: 10.1016/j.immuni.2008.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Conventional Dendritic Cells Is Compatible with Normal Development and T Cell Homeostasis, but Causes Myeloid Proliferative Syndrome

Abstract: Dendritic cells are critically involved in the promotion and regulation of T cell responses. Here, we report a mouse strain that lacks conventional CD11c(hi) dendritic cells (cDCs) because of constitutive cell-type specific expression of a suicide gene. As expected, cDC-less mice failed to mount effective T cell responses resulting in impaired viral clearance. In contrast, neither thymic negative selection nor T regulatory cell generation or T cell homeostasis were markedly affected. Unexpectedly, cDC-less mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
268
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 202 publications
(307 citation statements)
references
References 74 publications
(101 reference statements)
34
268
4
1
Order By: Relevance
“…Our data add to these findings and demonstrate that DCs are crucial regulators of polyclonal Treg proliferation. However, some have also argued that DCs may be dispensable for Treg generation and maintenance, because Treg frequency is normal in CD11c-DTa mice that constitutively lack DCs (41). In contrast, a recent report demonstrated that acute depletion of DCs in vivo results in decreased Treg numbers and proliferation, which leads to an increase in T cells that are competent to produce inflammatory cytokines (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data add to these findings and demonstrate that DCs are crucial regulators of polyclonal Treg proliferation. However, some have also argued that DCs may be dispensable for Treg generation and maintenance, because Treg frequency is normal in CD11c-DTa mice that constitutively lack DCs (41). In contrast, a recent report demonstrated that acute depletion of DCs in vivo results in decreased Treg numbers and proliferation, which leads to an increase in T cells that are competent to produce inflammatory cytokines (25).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent discrepancy may be explained by compensatory mechanisms that may be initiated in the constitutive absence of DCs, which allows a different cell type to substitute for DCs to maintain Treg homeostasis. Moreover, the physiologic proliferation of Tregs was not measured in the context of the constitutive absence of DCs (41).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing DC survival through transgenic expression of the baculoviral caspase inhibitor p35 or deletion of Fas leads to chronic lymphocyte activation and systemic autoimmunity (15,16), whereas increasing DC numbers by FMS-like tyrosine kinase 3 ligand (FLT3L) administration protects mice from autoimmunity via inducing regulatory T-cell (T reg ) accumulation (17)(18)(19). Conversely, constitutive ablation of cDCs through the expression of diphtheria toxin in CD11c + cells has been reported to cause fatal T-cell-mediated autoimmune disease (20) or a myeloid proliferative syndrome without obvious alterations of T-cell homeostasis (21). Mechanistically, peripheral DCs have been implicated in promoting homeostatic proliferation and survival of T cells (22)(23)(24) as well as inducing a low-level tonic signaling in naive T cells to program their responsiveness to foreign antigens (25).…”
mentioning
confidence: 99%
“…Mechanistically, peripheral DCs have been implicated in promoting homeostatic proliferation and survival of T cells (22)(23)(24) as well as inducing a low-level tonic signaling in naive T cells to program their responsiveness to foreign antigens (25). Moreover, although a direct role for DCs to promote T reg expansion and accumulation has been established by recent elegant studies (17,26), how this effect contributes to immune homeostasis is not fully understood (20,21,27,28). Because many of the previous studies have used nonphysiological approaches to modulate DC survival, how endogenous regulators of DC survival influence immune homeostasis and function remains to be established.…”
mentioning
confidence: 99%
“…However, the depletion of DCs does not affect thymic T-cell maturation and FoxP3 þ Treg generation, suggesting that the contribution of DCs to these processes is minimal. 34 Nevertheless, it is possible that DCs participate in the enforcement of tolerance to a specific subset of antigens or under specific conditions.…”
Section: Function Of Dcs In Cns Autoimmunitymentioning
confidence: 99%